Answer:
-2,-1
Explanation:
Solve the following system:
{y = 3 x + 5 | (equation 1)
x = -2 y - 4 | (equation 2)
Express the system in standard form:
{-(3 x) + y = 5 | (equation 1)
x + 2 y = -4 | (equation 2)
Add 1/3 × (equation 1) to equation 2:
{-(3 x) + y = 5 | (equation 1)
0 x+(7 y)/3 = -7/3 | (equation 2)
Multiply equation 2 by 3/7:
{-(3 x) + y = 5 | (equation 1)
0 x+y = -1 | (equation 2)
Subtract equation 2 from equation 1:
{-(3 x)+0 y = 6 | (equation 1)
0 x+y = -1 | (equation 2)
Divide equation 1 by -3:
{x+0 y = -2 | (equation 1)
0 x+y = -1 | (equation 2)
Collect results:
Answer: {x = -2 , y = -1